KARAKTERISTIK KADER DAN EVALUASI PELAKSANAAN KEGIATAN POSYANDU DIWILAYAH KERJA PUSKESMAS PEMBANTU KURAO KECAMATAN NANGGALO KOTA PADANG TAHUN 2019 - Ety Aprianti; Sri Suciana; Fery Musharyadi; Yona Firdali Ranti; Desi Noviayanti (HUMAN CARE JOURNAL, 2020)
Posyandu is a health service organized by, from, for and with the community. Padang DKK 2016 Puskesmas pembantu Kurao has a low Posyandu level. The purpose of this study was to find out the description of the implementation of the Kurao posyandu activity in the Working Area of Nanggalo Health Center in 2019.The purpose of this study was to find out how the Posyandu Cadre Characteristics and Evaluation of Posyandu Activity Implementation in the Work Area of the Kurao Sub-District Health Center in Nanggalo. This research is a quantitative and qualitative study using primary and secondary data obtained from Health Officers, cadres and the community who come to posyanduThe results obtained were more than half of respondents (56.6%) with the age category 26-45 years. Most respondents (80%) were married or married. More than half of respondents (63.4%) with <5 years old category. Most respondents (83.4%) with a secondary education level category. More than half of respondents (76.6%) in the category of not working or housewivesA total of 11 posyandu are under the working area of the Kurao Preparation of information on Posyandu implementation is carried out 1 day before the implementation of Posyandu and preparation of facilities, the infrastructure has been completed. In the implementation of posyandu activities, there was an ineffectiveness in the implementation of the fourth table because not all cadres understood and were able to provide counseling materials related to health issues, because not all cadres received specific training. Cadres only get information through regular monthly meetings at cadre social gathering events. The Posyandu Information System has been arranged in detail. Policies, preparation, implementation and Posyandu Information System in the work area of the Kurao sub-pustu have not been prepared and implemented in full, there are still shortcomings. With this research, it is recommended that health workers in the Puskesmas be able to provide training and refreshment to cadres and be able to complete all the deficiencies that exist in the implementation of the posyandu activities